2022
DOI: 10.1038/s41380-021-01430-5
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted social memory ensembles in the ventral hippocampus underlie social amnesia in autism-associated Shank3 mutant mice

Abstract: The ability to remember conspecifics is critical for adaptive cognitive functioning and social communication, and impairments of this ability are hallmarks of autism spectrum disorders (ASDs). Although hippocampal ventral CA1 (vCA1) neurons are known to store social memories, how their activities are coordinated remains unclear. Here we show that vCA1 social memory neurons, characterized by enhanced activity in response to memorized individuals, were preferentially reactivated during sharp-wave ripples (SPW-Rs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 60 publications
4
39
1
Order By: Relevance
“…We first confirmed previous reports that Shank3B KO mice have impaired sociability as well as impaired social discrimination memory (Peca et al, 2011; Tao et al, 2022). We utilized a three- trial direct social interaction test, with each trial separated by 24 hr, in which mice were exposed to a novel mouse (Novel 1) in trial 1, re-exposed to the same mouse (Familiar) in trial 2, and exposed to a second novel mouse (Novel 2) in trial 3 (Figure 1A).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We first confirmed previous reports that Shank3B KO mice have impaired sociability as well as impaired social discrimination memory (Peca et al, 2011; Tao et al, 2022). We utilized a three- trial direct social interaction test, with each trial separated by 24 hr, in which mice were exposed to a novel mouse (Novel 1) in trial 1, re-exposed to the same mouse (Familiar) in trial 2, and exposed to a second novel mouse (Novel 2) in trial 3 (Figure 1A).…”
Section: Resultssupporting
confidence: 90%
“…It remains possible that vCA1 SWRs might differ between WT and Shank3B KO mice but that the parameters of our recordings did not capture this effect. Along these lines, it is relevant to note that a recent study found diminished SWR amplitude in Shank3B KO compared to WT mice during the 2 hr rest period after social interaction, a time likely important for social memory consolidation (Tao et al, 2022). However, since the main difference we noted in social interaction between WT and Shank3B KO mice was with investigation of novel social stimuli, which does not involve memory consolidation or retrieval, it seems likely that this social novelty deficit is not dependent on differences in SWRs.…”
Section: Discussionmentioning
confidence: 99%
“…In Shank3 KO mice, reduced sociability has led to observed disruption of sharp‐wave ripples. Neurons activated during social behaviour underlying in the vCA1 were minor in Shank3 KO mice, which resulted in an inability to socially discriminate 53 …”
Section: Autism and Social Memorymentioning
confidence: 98%
“…Neurons activated during social behaviour underlying in the vCA1 were minor in Shank3 KO mice, which resulted in an inability to socially discriminate. 53 Defining the synaptic bases related to social behaviour would provide an insight to understand psychiatric disorders such as schizophrenia or depression, as this phenotype is articulated in a mouse model of autism. 53 Among the hippocampal subregions, dysfunction in CA1 is specific to schizophrenia, whereas dysfunction in CA2/CA3 is attributed to schizophrenia and bipolar disorder.…”
Section: Autism and Social Memorymentioning
confidence: 99%
See 1 more Smart Citation